Processos e resultados de empresas brasileiras após a certificação ambiental ISO 14001 - Avila, Gilberto Jesus (Universidade do Vale do Rio do Sinos)
This work had the objective to analyze the operational results achieved for ISO 14001 certificated Brazilians companies, and it was based in the environmental management and strategies of operations. To achieve this objective, the work found identifies the factors related to the operations process and the performance of operations after the environmental certification. The search method found to integrate both qualitative and quantitative analyses. The quantitative analysis was based on treatment of current statistics data that result of the participation of Brazilians companies in the DEVISO project (Developing Countries and ISO 14000). The qualitative analysis, in turn, used the personal interview to the Environmental Manager of the two companies that participated of the DEVISO project. The quantitative analysis was based on factor analysis (Principal Components Analysis – PCA) and comparison among means of factors that results through the paired sample t-tests. This analysis made possible to elaborate a pe
Keywords: desempenho das operações; estratégias de operações; processos de operação; gestão ambiental; ISO 14001; operations process; performance of operations; strategies of operations; environmental management; Ciências Sociais Aplicadas